Impact of Spray Drying Encapsulation on Metabolite Profile and Quality of Fish Oil Products - Novianty, Hilda; Anggraeni, Ayu Septi; Utami, Indrawati Dian; Kurniasih, Retno Ayu; Alam, Lucky Prabowo Miftachul; Oktaviyani, Selvia; Noerdjito, Diah Radini; Suratno, Suratno (Journal of Fisheries and Environment, 2025)
Encapsulation is one of the techniques to preserve fish oil compounds from deterioration and degeneration caused by oxidation. In the encapsulation process, the matrix wall protects fish oil substances, particularly when using the spray-drying method. This mechanism can induce changes in metabolite profiles while maintaining the quality of fish oil. In this study, metabolite changes were analyzed using high-performance liquid chromatography coupled with high-resolution mass spectrometry (HPLC-HRMS), alongside measurements of free fatty acids, acid values, and scanning electron microscope (SEM). The results showed distinct clusters between encapsulated and raw fish oil, with 75 metabolites identified, of which 35 were considered variables important in projection (VIP) metabolites. Statistical analysis revealed significant changes in 63 metabolites. Principal component analysis (PCA) clearly distinguished raw from encapsulated fish oil across a broad range, while the heatmap showed that most metabolites significantly differed among the treatment groups. PLS-DA identified 35 VIP metabolites, of which (1S,4S)-4-hydroxy-3-oxocyclohexanecarboxylic acid showed the highest VIP score. The VIP metabolites included 15 types of lipid derivatives, two amino acid derivatives, two carboxylic acid derivatives, two carbohydrate derivatives, two phenolic compounds, two aromatic compounds, and several minor substances. Additional findings showed a significant (p<0.05) decline in both free fatty acid and acid value levels for encapsulated fish oil, along with the formation of spherical encapsulated powder particles. The combination of HPLC-HRMS-based metabolomics with encapsulation analysis remains underexplored, and this study provides valuable insights into the encapsulation process for fish oil products.